TREATMENT OF RINGWOMB IN SHAMI GOATS - M., FATHALLA,; S.0., HUSSAIN (The Iraqi Journal of Veterinary Medicine, 1989)
Twenty Shami goats, aged 2-4 years at time of parturition were suffering from dystocia due to incomlete dilatation of the cervix (Ringwomb). 4 of them had preparturient prolagse of the vagina and cervix accompanying ringwomb. All animals were treated by manual dilatation of the cervix. 10 animals were given either a single intramuscular injection of 16 mg of Dexamthazone or 7.5mg of PGF2 analogue. Results of treatments indicaeted that dystocia was relieved in the following percent ages for different treatment. 10% (2 animals), 80% (8 animals), 100% (10 animals) and 100% (2 animals ) respectively. It may be concluded that hormonal treatment was superior to other form of treatment and both dexamethazone and prostaglandin F2 were almost equally effective in treatment of dystocia due to ringwomb in Shamigoats and can replace exposing the animals to major surgery.